Conocimiento y actitudes frente a los cambios en el régimen de lluvias por calentamiento global en estudiantes de Ingeniería en Gestión Ambiental, 2025 - Gamarra Oliveira, Jafed Fernando (2025)
This quantitative, correlational, and cross-sectional study analyzes the relationship between the level of scientific knowledge and environmental perception among ninth year Environmental Management Engineering students at the National University of the Peruvian Amazon (UNAP) in response to changes in rainfall patterns caused by global warming. This is a basic, non-experimental study in which variables are not manipulated but rather observed as they occur in reality. The sample was non probabilistic for convenience and included 37 students enrolled in the thesis course. A structured 22-item survey was used for data collection, with a high reliability (α = 0.848). Statistical analyses were performed using normality tests (Shapiro-Wilk) and Spearman correlation. The results indicate that students have an acceptable level of knowledge about environmental and climate issues, accompanied by positive attitudes toward sustainable actions such as reuse, recycling, and participation in environmental campaigns. However, institutional limitations are evident that restrict the implementation of effective environmental practices. It is concluded that there is a statistically significant and moderate relationship between scientific knowledge and environmental awareness, suggesting that a greater technical understanding of climate change translates into more committed attitudes toward environmental challenges.